Algorithmic Constitutionalism dan Masa Depan Hukum Tata Negara Indonesia: Menakar Batas Kekuasaan Algoritmik dalam Pengambilan Keputusan Publik - Mariyanti Mile; Roy Marthen Moonti (International Forum of Researchers and Lecturers, 2026)
The digital transformation of government has introduced algorithms and artificial intelligence as new instruments in public decision-making. This change raises constitutional issues because state decisions are no longer entirely implemented through officials and administrative procedures, but also through computational systems that are at risk of being closed, biased, discriminatory, and difficult to account for. This article aims to analyze the development of the concept of algorithmic constitutionalism and its relevance to the future of Indonesian constitutional law, particularly in limiting algorithmic power in the public sector. The method used is a literature review by examining books, journal articles, institutional reports, regulations, and policy documents related to digital constitutionalism, algorithmic governance, algorithmic accountability, personal data protection, and government administrative law. The analysis is conducted descriptively and qualitatively through concept identification, literature mapping, comparison of findings, and normative synthesis. The results of the review indicate that Indonesia already has a regulatory basis through the 1945 Constitution of the Republic of Indonesia, the Public Service Law, the Government Administration Law, the Public Information Disclosure Law, the Personal Data Protection Law, and the SPBE policy, but the regulations are still fragmented and do not specifically regulate the accountability of algorithm-based public decisions. This article concludes that public algorithms should be understood as a form of state power that must adhere to the principles of legality, meaningful transparency, the right to explanation, auditability, human control, non-discrimination, objection, remedy, proportionality, and public participation.